2020
DOI: 10.1186/s40885-019-0132-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and heart failure

Abstract: BackgroundHypertension is a leading cause of cardiovascular disease, stroke, and death. It affects a substantial proportion of the population worldwide, and remains underdiagnosed and undertreated.BodyLong-standing high blood pressure leads to left ventricular hypertrophy and diastolic dysfunction that cause an increase in myocardial rigidity, which renders the myocardium less compliant to changes in the preload, afterload, and sympathetic tone. Adequate blood pressure control must be achieved in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 69 publications
2
72
0
4
Order By: Relevance
“…Heart failure has been identified as a comorbidity but not a protective factor [31]. There is no clear interpretation of the risk of ICH in the context of heart failure or of the role of low blood pressure as a preventive factor for ICH because the data describing the optimal BP goals in patients with HF are limited and contradictory [32,33]. However, the risk of ICH could be related to the concurrence of atrial fibrillation and a greater or lesser indication of antiplatelet and anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure has been identified as a comorbidity but not a protective factor [31]. There is no clear interpretation of the risk of ICH in the context of heart failure or of the role of low blood pressure as a preventive factor for ICH because the data describing the optimal BP goals in patients with HF are limited and contradictory [32,33]. However, the risk of ICH could be related to the concurrence of atrial fibrillation and a greater or lesser indication of antiplatelet and anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension (HTN), also known as high blood pressure (BP), can be classified into primary or secondary HTN with secondary HTN affecting 5–10% of hypertensive patients with the cause linked to an underlying medical condition. In contrast, primary hypertension also known as essential HTN accounts for 90–95% of HTN cases, it has no identifiable secondary root and is the most common cause of stroke and cardiovascular disease (CVD) [ 1 , 2 ]. Accumulative evidence showed that the prevalence of HTN is 1.3 billion, and this number is projected to increase to 1.56 billion by 2030 with an estimated global economic cost of $274 billion [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in Thailand among hypertensive patients in Bangkok showed that although hypertensive patients were aware of their uncontrolled hypertension, they still chose to have a high salt diet due to a preference for tastier and instant food [ 48 ]. The pattern of the findings from other countries was similarly observed, such as in Ethiopia [ 49 , 50 ], Nepal [ 42 ], India [ 51 , 52 ], Australia [ 53 ], Iran [ 54 , 55 ], Spain [ 56 ], and Korea [ 57 ]. These studies revealed that individuals generally have a reasonable knowledge of the salt and its adverse effects of overconsumption as well as their favorable attitudes toward salt reduction; however, almost none of them took action to reduce salt intake, and their blood pressure was still uncontrolled.…”
Section: Discussionmentioning
confidence: 57%